Expression of immuno-transcriptome response in red hybrid tilapia (Oreochromis sp.) hindgut following vaccination with feed-based bivalent vaccine - Mohd Ali, Nur Shidaa; Ngalimat, Mohamad Syazwan; Saad, Mohd Zamri; Azmai, Mohammad Noor Amal; Salleh, Annas; Zulperi, Zarirah; Md Yasin, Ina Salwany (John Wiley and Sons, 2024)
Streptococcosis and aeromoniasis are the main obstacles to sustainable tilapia pro- duction. Vaccination offered an effective method to control microbial infections. Previously, a feed-based bivalent vaccine (FBBV) containing killed whole organisms of Streptococcus agalactiae and Aeromonas hydrophila mixed with 10% palm oil was successfully developed, which provided good protection against streptococcosis and aeromoniasis in Oreochromis sp. However, the mechanisms of immunities in vacci- nated fish still need clarification. Here, the hindgut transcriptome of vaccinated and control fish was determined, as the gut displays higher affinity towards antigen uptake and nutrient absorption. The efficacy of FBBV to improve fish immunity was evalu- ated according to the expression of immune-related genes in the vaccinated fish hind- gut throughout the 8-week experimental period using RT-qPCR. The vaccinated fish hindgut at week 6 was further subjected to transcriptomic analysis due to the high expression of immune-related genes and contained killed whole organisms. Results demonstrated the expression of immune-related genes was in correlation with the presence of killed whole organisms in the vaccinated fish hindgut. Transcriptomic analysis has allowed the prediction of robust immune-related pathways, including in- nate and adaptive immunological responses in vaccinated fish hindgut than control fish. Pathways related to the regulation of lipid metabolism and modulation of the immune system were also significantly enriched (p ≤ .05). Overall, results offer a fun- damental study on understanding the immunological response in Oreochromis sp. fol- lowing vaccination with the FBBV pellet and support further application to prevent bacterial diseases in aquaculture.